1980
DOI: 10.1128/jb.141.1.1-9.1980
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth rates of Candida utilis mother and daughter cells under phased cultivation

Abstract: The yeast Candida utilis was continuously synchronized by the phased method of cultivation with the nitrogen source as the growth-limiting nutrient. The doubling time (phasing period) of celLs was 6 h. Both cell number and deoxyribonucleic acid synthesis showed a characteristic stepwise increase during the phased growth. The time of bud emergence coincided with the time of initiation of deoxyribonucleic acid synthesis. Size distribution studies combined with microscopic analysis showed that the cells expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The shape of the cells was assumed to be a prolate spheroid, and the volumes were calculated by using the formula V=(π/6)lw 2 , where V is the volume, l is the height, and w is the width at maximum circumference (diameter) (Johnston et al, 1977). Thomas et al (Thomas et al, 1980) reported about 38% difference in cell volume between fully separated mother and daughter cells of Candida utilis type of yeast cell. In our experiment, the volume difference of the mother and daughter cells is about 45% and this is reasonable since the daughter was not fully grown as it was still intact with its mother at the time of measurement.…”
Section: Application Of Hard Nanoneedle: Single Cell Local Stiffness mentioning
confidence: 99%
“…The shape of the cells was assumed to be a prolate spheroid, and the volumes were calculated by using the formula V=(π/6)lw 2 , where V is the volume, l is the height, and w is the width at maximum circumference (diameter) (Johnston et al, 1977). Thomas et al (Thomas et al, 1980) reported about 38% difference in cell volume between fully separated mother and daughter cells of Candida utilis type of yeast cell. In our experiment, the volume difference of the mother and daughter cells is about 45% and this is reasonable since the daughter was not fully grown as it was still intact with its mother at the time of measurement.…”
Section: Application Of Hard Nanoneedle: Single Cell Local Stiffness mentioning
confidence: 99%
“…The shape of the cells was assumed to be a prolate spheroid, and the volumes were calculated by using the formula V=(π/6)lw 2 , where V is the volume, l is the height, and w is the width at maximum circumference (diameter) (Johnston et al, 1977). Thomas et al (Thomas et al, 1980) reported about 38% difference in cell volume between fully separated mother and daughter cells of Candida utilis type of yeast cell. In our experiment, the volume difference of the mother and daughter cells is about 45% and this is reasonable since the daughter was not fully grown as it was still intact with its mother at the time of measurement.…”
Section: Application Of Hard Nanoneedle: Single Cell Local Stiffness Characterizationmentioning
confidence: 99%
“…One portion is retained in the reactor for the subsequent cycle and the other is made available for "post-cycle'' studies (Dawson, 1969(Dawson, , 1970 and, unlike a pulsed chemostat, the entire nutrient environment is cycled, not just a single nutrient. The technique has been applied primarily to study cell cycle events in Candida utilis by Muller and Dawson (1968), Hampton and Dawson (1969), Dawson (1971Dawson ( , 1985b, Dawson et al (1976) and Thomas et al (1980aThomas et al ( , 1980b, but has also been used with E. coli (Anagnostopoulos, 197 1;Kepes andKepes, 1980, 1985), and B. subtilis (Maruyama et al, 1977). Figure 4 illustrates the type of data that can be collected from a continuous phased culture (Dawson, 1988), in this case Candida utilis with a cell cycle of 4 h duration followed by an 8 h post cycle period.…”
Section: Phased Culturementioning
confidence: 99%